2014
DOI: 10.1182/blood-2014-03-560557
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, phase 2 trial of low-dose cytarabine with or without volasertib in AML patients not suitable for induction therapy

Abstract: Key Points• Volasertib plus low-dose cytarabine increased the response rate and improved survival in AML patients ineligible for intensive treatment.• Volasertib plus low-dose cytarabine resulted in responses across all AML genetic subgroups and had a clinically manageable safety profile.Treatment outcomes for older patients with acute myeloid leukemia (AML) have remained dismal. This randomized, phase 2 trial in AML patients not considered suitable for intensive induction therapy compared low-dose cytarabine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(176 citation statements)
references
References 36 publications
7
167
1
1
Order By: Relevance
“…Early clinical studies in patients with solid tumors had indicated that the compound has therapeutic potential and is well tolerated (Gjertsen and Schoffski, 2015), with mainly hematologic toxicities and the notable absence of neuropathies, and thus may be particularly beneficial for patients unable to tolerate aggressive chemotherapy. Importantly, recent clinical data in AML patients showed that volasertib combined with low-dose cytarabine (LDAC) was associated with higher response rates and improved event-free survival than LDAC alone (Dohner et al, 2014). On this basis, volasertib in combination with LDAC is currently being evaluated in a phase III clinical study in patients with previously untreated AML who are ineligible for intensive therapy (NCT01721876; POLO-AML-2).…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical studies in patients with solid tumors had indicated that the compound has therapeutic potential and is well tolerated (Gjertsen and Schoffski, 2015), with mainly hematologic toxicities and the notable absence of neuropathies, and thus may be particularly beneficial for patients unable to tolerate aggressive chemotherapy. Importantly, recent clinical data in AML patients showed that volasertib combined with low-dose cytarabine (LDAC) was associated with higher response rates and improved event-free survival than LDAC alone (Dohner et al, 2014). On this basis, volasertib in combination with LDAC is currently being evaluated in a phase III clinical study in patients with previously untreated AML who are ineligible for intensive therapy (NCT01721876; POLO-AML-2).…”
Section: Discussionmentioning
confidence: 99%
“…96 In a recent randomized trial comparing low-dose cytarabine with or without volasertib in older patients ineligible for intensive therapy, the combination therapy doubled the response rate and even showed a signal for a survival benefit. 97 A pivotal placebo-controlled phase 3 trial in this patient population is ongoing (www.ClinicalTrials.gov identifier NCT01721876) and a randomized phase 2 trial evaluating volasertib in combination with intensive therapy, including younger adult patients (18 years and older) with newly diagnosed AML, is in the planning phase (www.ClinicalTrials.gov identifier NCT02198482).…”
Section: Mll-rearranged Aml and Dot1l Inhibition Deregulation Inmentioning
confidence: 99%
“…27 The dose of volasertib was 350 mg on days 1 and 15 of a 28-day cycle. CRc was 31% in the combination arm compared with 13.3% with LDAC monotherapy with a strong trend toward statistical significance (P 5 .052).…”
Section: Molecularly Targeted Agentsmentioning
confidence: 99%